Tsunami impacts on groundwater and water supply in eastern Sri Lanka - Villholth, Karen G. (Practical Action Publishing, 2007)
Most households in the districts of Sri Lanka affected by the tsunami possessed drinking water wells, and these wells were contaminated by debris, sludge and saltwater. Once the wells were cleaned, only time and the onset of monsoon rains could reduce the levels of salinity - but local people continued to need information and reassurance about the quality of their water supplies.